An overview of meat processing in Africa - Rich, Karl M.; Schaefer, K. Aleks; Thapa, Bhawna; Hagerman, Amy D.; Shear, Hannah E. (AKADEMIYA2063, 2022)
Relative to the literature on live animal production and trade, research on the meat processing sector in Africa is particularly sparse. This belies a sector that is increasingly dynamic, driven by changing demand patterns, evolving marketing channels, and population growth. This chapter aims to redress some of the research gaps by piecing together available data from countries south of the Sahara, combined with a series of case studies, to illustrate the rapid changes that are taking place within the sector. Our analysis focuses on meat as an end product only and does not consider other products derived from animals, notably dairy, where a significant literature exists (particularly in East Africa), and by-products such as hides and skins. We also highlight many of the important constraints affecting the sector to raise awareness of critical policy issues and draw attention to the integrated nature of animal end products alongside livestock production.